2001
DOI: 10.1007/s000110050723
|View full text |Cite
|
Sign up to set email alerts
|

Dithranol upregulates IL-10 receptors on the cultured human keratinocyte cell line HaCaT

Abstract: Since the interleukin-10 receptor expression of keratinocytes in psoriatic lesional skin is downregulated, the dithranol induced upregulation of the receptor in our model system might help to reveal the therapeutic action of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…HaCaT, an immortalized cell line of human epidermal keratinocytes (Boukamp et al, 1988), which has been extensively used as an in vitro model for studies on the pathogenesis of psoriasis and evaluation of antipsoriatic drugs (Garach-Jehoshua et al, 1999;Farkas et al, 2001;Thielitz et al, 2004), was provided by the China Centre for Type Culture Collection (Wuhan, China). Hs-68, a human fibroblast cell line established from the foreskin of a normal Caucasian newborn male, was purchased from the American Type Culture Collection (Manassas, VA).…”
Section: Methodsmentioning
confidence: 99%
“…HaCaT, an immortalized cell line of human epidermal keratinocytes (Boukamp et al, 1988), which has been extensively used as an in vitro model for studies on the pathogenesis of psoriasis and evaluation of antipsoriatic drugs (Garach-Jehoshua et al, 1999;Farkas et al, 2001;Thielitz et al, 2004), was provided by the China Centre for Type Culture Collection (Wuhan, China). Hs-68, a human fibroblast cell line established from the foreskin of a normal Caucasian newborn male, was purchased from the American Type Culture Collection (Manassas, VA).…”
Section: Methodsmentioning
confidence: 99%
“…Dithranol treatment was performed following a procedure previously described by Farkas et al (2001) with minor modifications (Tencomnao et al, 2009). In brief, cultured HaCaT cells at about 90% confluence in a 60-mm plate were washed with phosphate buffered saline (PBS) under sterile conditions and were incubated for 30 min at 37°C in a humidified atmosphere at 5% CO 2 with increasing concentrations of dithranol (0.1, 0.25 and 0.5 mg/mL) (Sigma, St. Louis, MO, USA) in DMEM containing 0.5% FBS.…”
Section: Dithranol Treatmentmentioning
confidence: 99%
“…Therefore, this particular cell line could be considered a promising tool for studying the regulation of keratinization in human cells (Boukamp et al, 1988). The HaCaT cell line was chosen for this study since it has been demonstrated to be a suitable cellular model of psoriasis according to previous reports (Farkas et al, 2001;Tencomnao et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…HaCaT cell line, which is a spontaneously immortalized line of human epidermal keratinocytes that exhibits normal differentiation (5) and has been extensively used as an in vitro model for the studies of psoriasis (6)(7)(8), was obtained from the China Centre for Type Culture Collection, Wuhan, Hubei Province, China. The HaCaT cells were routinely maintained in DMEM supplemented with 10% FCS, 10 μg/ml streptomycin and 10 U/ml penicillin and incubated at 37˚C in a 5% CO 2 , 95% air humidified atmosphere.…”
Section: General Cell Culturementioning
confidence: 99%